Effects of indoor relative humidity on volatile organic compound emissions of new and aged Scots pine wood - Sivula, Arttu; Heräjärvi, Henrik; Harju, Anni; Pasanen, Pertti; Möttönen, Veikko; Hyttinen, Marko (SAGE, 2025)
This article reports the variations in volatile organic compound (VOC) emission rates from Scots pine wood under varying relative humidity (RH) conditions. The experiment encompassed both heartwood and sapwood, involving recently sawn (“new”) wood, and aged (“old”) wood that had been stored indoors for 15 years. Individual specimens were placed in climate chambers, wherein specific RH levels were maintained in the following sequence: 20%, 40%, 60%, 80%, 60%, 40%, and 20%, 1 month each. VOC samples were systematically collected at the end of each RH period and analyzed using TD-GC-MS system. The results demonstrate a direct relationship between RH levels and VOC emission rates in all specimen categories. Old wood indicated significantly lower emission rates compared to new wood, with distinct differences in emitted compound composition. As the experiment progressed, the initial differences between old and new specimens diminished, reaching minimum difference by the last measurement. Aldehydes were among the two most prevalent compound groups in all sample types. Terpenes were the most abundantly emitted group during the first VOC collection. However, their emissions subsequently declined, followed by an increase in all main chemical groups at 80% RH. Additionally, more polar compounds were emitted as RH increased. This study contributes to the discussion regarding the suitability of standard emission tests performed in fixed 50 ± 5% RH for hygroscopic materials. More attention should be given to the influence of RH on VOC emissions to ensure a comprehensive understanding of wood material’s emission behavior.
Keywords: indoor air quality; relative humidity; VOC; emissions; Scots pine; untreated wood